Efek Perlakuan Jenis Pupuk Kandang dan Komposisi Biochar Sekam Padi yang Berbeda dalam Kompos Terhadap Pertumbuhan dan Hasil Sawi (Brasicca Juncea L.) Di Tanah Vertisol - Sofia Ari Serfina Bani; Eduardus Yosef Neonbeni (Savana Cendana, 2022)
This study aims to determine the effect of biochar and manure on the growth and yield of mustard greens in vertisol soil, determine the effect of biochar on the growth and yield of mustard greens in vertisol soil, determine the effect of manure on the growth and yield of mustard greens verttisol soil. This research was conducted from July to September 2020 at the Faculty of Agriculture, University of Timor. Sasi Village, Bikomi Selatan District, Kefamenu City, North Central Timor Regency. This research used a completely randomized design (CRD) with 2 factors. The planting factor is the type of manure (K) which consists of no manure (K0), cow manure (K1), goat manure (K2). The second factor is the treatment of manure (P) which consists of (P1) 10% biochar composition of rice husk, (P2) 20% biochar composition of rice husk, (P3) 30% composition of rice husk biochar. So that the combination of K0P1, K0P2, K0P3, K1P1, K1P2, K1P3, K2P1, K2P2, K2P3 treatments is obtained. which was repeated 4 times in order to obtain the number of treatment combinations as many as 36 experimental units. The results showed that, the treatment of goat manure was the best treatment for the growth and yield of mustard greens (Brassica juncea L.). The results showed that the treatment of 10% biochar compost gave the best value for growth and yield of mustard greens. (Brassica juncea L.).